Avaliação de métodos de preparo de amostras para a determinação de elementos terras-raras em insetos comestíveis por USN-ICP-MS - Rocha, João Lucas Kipper (2023)
In this work, three sample preparation methods were evaluated for the subsequent determination of rare earth elements (REE) in insects using inductively coupled plasma mass spectrometry (ICP-MS). To avoid possible interferences in the REE determination step, an ultrasonic nebulizer (USN) was coupled to the ICP-MS equipment. The methods evaluated were: i) microwave-assisted wet digestion (MAWD) with diluted acids, ii) microwave-assisted ultraviolet digestion (MAWD-UV) and iii) microwave-induced combustion (MIC). In MAWD, up to 500 mg of sample were decomposed with a heating time of 60 min and using 5 mol L-1 of HNO3 + 1 mL of 12 mol L-1 of HCl. For MAWD-UV, up to 500 mg of sample mass were decomposed with a heating time of 60 min using a solution of 3 mol L-1 of HNO3 + 1 mL of 12 mol L-1 of HCl. For MIC method, up to 500 mg of sample were digested with a heating program of 35 min and using aqua regia as absorbing solution. Three samples of edible crickets from China, Brazil and Thailand were used. To obtain reference values, the cricket samples were digested using the following methods: i) MAWD with 14.4 mol L-1 HNO3 and ii) conventional wet digestion in open system (CWD-OS). However, due to the relatively high limits of quantification (LOQs) obtained for CWD-OS, MAWD with 14.4 mol L-1 HNO3 was chosen as the reference method, allowing the comparison of a higher number of analytes for all samples. To evaluate the accuracy of the proposed methods, a certified reference material of mussel tissue (CRM BCR-668) was used. The results obtained for CRM, using the three proposed methods, showed no significant difference with the certified value (p > 0.05). The results obtained after the determination of the REE did not show significant difference (p > 0.05) between the three proposed methods and the reference method. During the evaluation of the methods, it was observed that only using HCl in the decomposition/absorbing solution it was possible to quantitatively retain the REE in solution, possibly due to the presence of insoluble species of these elements, which makes complete solubilization difficult when diluted HNO3 is used. MAWD and MAWD-UV allowed the use of diluted solutions and lower LOQs, while with MIC it was possible to decompose with shorter preparation time and lower carbon contents in solution (< 18.3 mg L-1 ). The limits of quantification (LOQs) obtained for the evaluated methods were relatively low: between 0.12 ng g-1 (Eu) and 21.8 ng g-1 (La) for MAWD, between 0.15 ng g-1 (Eu) and 37.3 ng g-1 (Ce) for MAWD-UV and between 1.58 ng g-1 (Eu) and 69.4 ng g -1 (Ce) for MIC. Finally, all three methods were suitable for the decomposition of up to 500 mg of cricket samples, enabling the determination of REE by USN-ICP-MS.